Dila ng bayan - Medina, Isagani Ramos 1930-; Philippines. National Commission for Culture and the Arts. Committee on Language and Translation (Manila National Commission for Culture and the Arts, Committee on Language and Translation, 2005)
"Dila ng Bayan is a collection of three interrrelated articles on language history and culture by Dr. Isagani R. Medina, professor emeritus, U.P. Department of History, College of Social Sciences and Philosophy. He himself gave the title for this book, which forms part of the "Mga Ani ni Gani" Series---a five-volume compilation of his essays written from 1951 to 1995."--Preface.
Vocabularios y diccionarios in the major and minor Philippine languages : lasting legacies of the Church in the Philippines (1565-1898) -- Major languages : Luzon -- Bisayan Islands -- Palawan (Cuyo) -- Mindanao and Sulu -- Minor languages -- Ang kasaysayang panlipunan ng Pilipinas : isang rekonstruksyon mula sa mga diskyunaryo't bokabularyong tagalog, 1600-1914 -- Pagninilay sa mahal na araw ukol sa "dalamhati," "luwalhati" at "ginhawa" sa Mahal na Passion ni Jesu Christo ng 1760.
Keywords: Philippine languages -- History; Language and culture -- Philippines